Antioxidant metabolism insights into ripening and senescence delay of green pepper fruit through the salicylic acid preharvest treatment - Dobón-Suárez, Alicia; Gutiérrez-Pozo, María; Serna-Escolano, Vicente; Giménez, María J.; Valero, Daniel; Serrano, María; García-Pastor, María E.; Zapata, Pedro J. (Frontiers in Plant Science, 2025)
IntroductionThe systematic investigation of the biochemical and molecular bases of salicylic acid (SA) in the postharvest physiological process of green pepper fruit remains unclear.MethodsAccordingly, this study aims to analyze the effects of 0.5 mM-SA preharvest treatments, applied by foliar spraying or irrigation, on the ripening and senescence of green pepper fruit for 28 days of storage at 7 °C.ResultsThe study revealed that the preharvest application of SA, either by foliar spraying or irrigation, significantly delayed losses of weight, firmness and color during postharvest. Additionally, both treatments increased the total soluble solids and total acidity content, which lead to a significantly reduced ripening index after storage. These results were evidenced by a slowing down of the ripening and senescence processes, accompanied by the stimulation of the antioxidant enzymes in those SA-treated green pepper fruits. Furthermore, a significant increase in chlorophylls, phenolics, ascorbic acid and dehydroascorbic acid content was observed. The SA treatments also enhanced the total antioxidant activity, in both hydrophilic and lipophilic phases. These positive effects were mediated by the upregulation of the relative response of the CaAPX, CaPOD, CaPAL, CaDHAR2 genes at harvest.DiscussionThese findings reinforce the existing knowledge gap regarding the impact of foliar spraying or irrigation SA on the intricate interplay between metabolites and genes related to the antioxidant system in regulating the bell pepper fruit ripening and senescence. The impact of both applications exhibited comparable results; however, the irrigation was identified as the most advantageous due to its ease applicability and cost effectiveness in comparison.